Profile of The Role of The Principal in Guidance and Counseling in SMP Muhammadiyah 6 Padang - Julinar, Nicky yulizar; Zulkifli; Joni Adison (Jurnal Riset Ilmu Pendidikan, 2022)
The background of this research is to determine the role of the principal in a school, especially in guidance and counseling. The purpose of this study was to determine 1) the role of the principal in coordinating the programed BK activities. 2) be responsible for implementing BK services in schools. 3) facilitate, provide opportunities and provide support to BK teachers. 4) provide support for every program implemented by the BK teacher. 5) give opinions to the BK teacher on the BK plan. 6) carry out monitoring and evaluation activities. This study uses research methods using a qualitative descriptive approach. Data collection techniques used are interviews and observation. The subject of this research is the principal of SMP Muhammadiyah 6 Padang. The researcher acts as a direct interviewer to collect data through key informants, namely the principal and additional informants, namely the BK Coordinator. The data analysis technique used is data reduction, data presentation, conclusion drawing and verification. The findings of the study are: 1) The role of the principal in Guidance and Counseling is seen from coordinating the BK activities programmed by the BK teacher. 2) Accountability for implementing BK services in schools is appropriately marked by the principal seeing the BK room for the BK service process. 3) Providing facilities are still incomplete, marked by the BK room which is very small and narrow. 4) Provide support for the programcarried out by the BK teacher positively and provide input that builds the morale of the BK teacher. 5) Giving his opinion on the plan made by the BK teacher can provide new ideas to facilitate/simplify the plan that will be implemented by the BK teacher. 6) Carry out monitoring and evaluation activities that have been carried out well by looking at the program made by the BK teacher. In conclusion, the principal plays a role in assisting the process of BK services in schools. Suggestions for school principals to play a greater role in the BK service process in schools and provide more adequate facilities and infrastructure.